Parkchain: A Blockchain Powered Parking Solution for Smart Cities - Jennath, H. S.; Adarsh, S.; Chandran, Nikhil V.; Ananthan, R.; Sabir, A.; Asharaf, S. (Frontiers in Blockchain, 2019)
With the advances happening in the area of urbanization, with increased demand for dwellings and ever growing number of vehicles on road, finding a parking spot has become one of the major pain points for the citizens. This is mainly due to the limited parking spaces in the urban areas. To overcome this limitation, one solution is to create more parking spaces. In this work we propose a Blockchain based solution, where parking pools can be created by developing a transparent platform where individuals can rent out their unused land for a stipulated amount of time with little or no legal hassles. A non-fungible token system representing unique parking lots will be created for transparency of the entire system. This also has the added advantage of generating revenue from their otherwise unused property. Smart contracts over Blockchain enforces the contractual agreement between the participants ensuring financial transparency in the proposed system.